Is GSH Chelated Pt Molecule Inactive in Anti‐Cancer Treatment? A Case Study of Pt6GS4. Issue 26 (5th June 2020) - Zhang, Chunyu; Gao, Liang; Yuan, Qing; Zhao, Lina; Niu, Wenchao; Cai, Pengju; Li, Jiaojiao; Han, Xu; He, Zhesheng; Gao, Fuping; Wang, Yaling; Jiang, Huaidong; et al.
Abstract: Platinum (Pt) drugs are widely used in anti‐cancer treatment although many reports advocated that tumor cells could inactivate Pt drugs via glutathione‐Pt (GSH‐Pt) adducts formation. To date, GSH chelated Pt molecules have not been assessed in cancer treatment because GSH‐Pt adducts are not capable of killing cancer cells, which is widely accepted and well followed. In this report, endogenous biothiol is utilized to precisely synthesize a GSH chelated Pt molecule (Pt6 GS4 ). This Pt6 GS4 molecule can be well taken up by aggressive triple negative breast cancer (TNBC) cells. Subsequently, its metabolites could enter nuclei to interact with DNA, finally the DNA‐Pt complex triggers TNBC cell apoptosis via the p53 pathway. Impressively, high efficacy for anti‐cancer treatment is achieved by Pt6 GS4 both in vitro and in vivo when compared with traditional first‐line carboplatin in the same dosage. Compared with carboplatin, Pt6 GS4 keeps tumor bearing mice alive for a longer time and is non‐toxic for the liver and kidneys. This work opens a route to explore polynuclear Pt compound with accurate architecture for enhancing therapeutic effects and reducing systemic toxicity. Abstract : Previous reports have advocated that cancer cells could utilize endogenous GSH to chelate Pt drugs to produce inactive GSH‐Pt adduct. Herein, a GSH chelated Pt molecule is precisely synthesized, which exhibits efficient cancer therapy without systemic toxicity in vivo. This work opens a route to explore polynuclear Pt compounds with accurate architectures as promising anti‐tumor agents.